Systems for anticipation of skill needs in the EU Member States - (:unkn) unknown (My University, 2008)
Dieses Arbeitspapier wurde im Kontext der Initiative "New skills for new Jobs" erstellt. Die Initiative wurde im Juli 2008 vorgestellt und versucht unter anderem die gefragten Fähigkeiten auf dem Arbeitsmarkt bis 2020 in der EU abzuschätzen. Um die Europäische Kommission in ihrer politischen Arbeit zu unterstützen fertigte Cedefop 2007/08 auf Grundlage von Berichten der meisten EU-Staaten über ihre jeweiligen Arbeitsmarktsituationen dieses Arbeitspapier an. Die ReferNet-Länder stellten ihr System und die Nachfrage nach Kompetenzen anhand von Fragen dar, sodass Cedefop die Daten der Länder miteinander vergleichen konnte. (BIBB-Doku)

"This working paper has been prepared in the context of the ´New skills for new jobs´ initiative which was introduced and presented in the July 2008 Communication on the renewed social agenda for opportunities, access and solidarity the Councils and European Council requests to the Commission to present a comprehensive assessment of the future skills requirements in Europe up to 2020 and to propose further steps to anticipate future needs. To support the European Commission, Cedefop reviews in this paper systems for anticipation of skill needs in the EU Member States. The reports were produced in 2007/08 on the basis of templates which asked Member States via ReferNet to describe their systems of anticipation of skill needs answering a range of questions. Even though the coverage is still not entirely comprehensive, the database which resulted from the exercise provides a unique opportunity to gather comparable information across countries." (Hrsg)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 2.3.4 Qualifikationswandel; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.2 Europa; Früherkennung; Qualifikationsanforderung; Kompetenz; Kompetenzbewertung; Schlüsselqualifikation; Arbeitsmarktsituation; Arbeitsmarktanalyse; Europa